Process development and techno-economic analysis of co-production of colorants and enzymes valuing agro-industrial citrus waste - Lima, Caio A. [UNESP]; Bento, Heitor B.S. [UNESP]; Picheli, Flávio P. [UNESP]; Paz-Cedeno, Fernando R. [UNESP]; Mussagy, Cassamo U.; Masarin, Fernando [UNESP]; Torres Acosta, Mario A.; Santos-Ebinuma, Valéria C. [UNESP] (Elsevier, 2023)
Valorization of waste generated during industrial process has gained considerable attention in recent years. The citrus industry produces high amount of waste that can be used to obtain biomolecules with significant economic value. This study aims to investigate the potential of citrus by-product (CB) as carbon source for the co-production of red colorants (RC) and enzymes by the filamentous fungi Talaromyces amestolkiae in submerged cultivation using an orbital shaker. The microorganism was able to metabolize the CB employing their sugars as carbon source to the production of RC achieving a colorant yield of 0.016 g.L−1h−1 for batch when the culture media was supplemented with glucose and glutamate monosodium. Alongside the production of colorants, the microorganism also produced enzymes, including endo-glucanases, xylanase, and β-glucosidase (with the latter being the most abundantly produced, specifically 2.8 U/mL). Although the economic analysis of the process indicated that further improvements are required to make the current production of this colorant economically viable, especially if citrus waste is utilized as the main source material. Considering a biorefinery approach, the results achieved in this study are quite promising, given the generation of high commercial value commodities, such as natural colorants and enzymes, using citrus by-product.
Keywords: Biorefinery; Cellulases and hemicellulases enzymes; Economic analysis; Fungi; Polyketides colorants; Waste valorization